IMPLEMENTASI PERATURAN DAERAH KABUPATEN INDRAGIRI HILIR NOMOR 3 TAHUN 2018 TENTANG TATA NIAGA KELAPA - Iskandar, Dedy; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Regional Regulation Indragiri Hilir Regency No 3 of 2018 on Commerce Coconutsit isimportant because the coconut is a potential preeminent that can enhance the well being of coconut farmers at Indragiri HIlir Regency. Observations from the field have some concern about Implementation Regional Regulation Indragiri Hilir Regency No 3 of 2018 on Commerce Coconut. The main objektive of study is to examine the Implementation of Regional Regulation Indragiri Hilir Regency No 3 of 2018 on Commerce Coconuts and any limiting factor A George C. Edward III Riant Nugroho (2009:636). Is used to determine the sample of the research. The methods of the research is qualitative research by using approach case studies. To coliect the data in this research were interview, observation, documentation. It was found that the Implementation of Regional Regulation Indragiri Hilir Regency No 3 of 2018 on Commerce Coconut havent received yet because there are some contributing factors that theres no price for the words reference to coconuts as free stuff, based on suply and demand the govermant cant adjust the price margins of the coconuts between the coconut growers and the coconut manager meanwhile, the inhibitory factor is that of uncreative human resources it is better for the Indragiri Hilir Goverment to cooperate with coconuts businessmen and coconuts companies to implement The Regional Regulation No 3 of 2018 on Commerce coconuts. Keywords: Implementation, Regional Regulation, Commerce Coconuts.